Evaluation of SIFs for cracks under thermal impact based on Green-Naghdi theory. (June 2020) - Nazari, Mohammad Bagher; Mahdizadeh Rokhi, Masoud
Highlights: XFEM analysis of cracks under thermal shock based on Green- Naghdi theory is carried out. The time history of temperature and thermal SIFs based on Green- Naghdi models with classic and Lord- Shulman theories are compared. The effect of damping coefficient on the time history of temperature and stress intensity factors is studied. Abstract: This paper presents a study on the crack behavior under a thermal shock in a wide range of applications. The Stress Intensity Factors (SIFs) for a stationary crack under a non-Fourier thermal shock according to the Green-Naghdi (GN) theory is computed. The crack is considered as an adiabatic line in the framework of the eXtended Finite Element Method. The interaction integral is employed to extract the SIFs for three types of the Green-Naghdi theory. The differences in the time history of SIFs due to the thermal shock based on all types of the GN theory is studied. Also, the effect of damping coefficient on the SIFs and the temperature field is investigated. Finally, the role of inclined cracks, which disturb the time history of SIFs, displacement and temperature distributions for type II and III of the GN theory are discussed.